Upaya Meningkatkan Displin Belajar Siswa Dengan Konseling Kelompok Behavior Contract - Della Wakhosyiyah Rohmana; Fakhruddin Mutakin; Siti Ernawati (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
Teachers must be able to create discipline in students, such as helping students improve their standards of behavior and using the application of rules as a tool to strengthen discipline in learning activities. Therefore, for the success of education, discipline in learning activities for students in the teaching and learning process is absolutely necessary. This type of research is qualitative research based on guidance and counseling action research conducted in 2 cycles. The subjects of this study amounted to 6 members in one group. The methods used in data collection are observation, questionnaires, interviews. Sampling in this study used purposive sampling, namely population sampling was carried out based on criteria determined by the researcher. Based on the results of observations, the results obtained are that the level of student discipline is relatively low. In cycle I the result was an increase in career planning in the medium category by 73% and in cycle II the results were in the highest category which was 95%. So it can be explained that the provision of group counseling services using the behavior contract technique can improve the learning discipline of class VIII students of MTs Al Khoiriyah Keyword: Learning discipline; behavioral contract group counseling